Романівський просвітянський осередок у 1920-х – початку 1930-х років - Сорока, Юрій; Soroka, Yurii (My University, 2016)
У статті розкрито історію створення та діяльності одного з перших культурно-освітніх товариств на Волині – «Просвіти» – у с. Романів Луцького повіту. Установлено, що воно було важливим осередком економічного та культурного відродження українського народу, сприяло його освітньому й духовному розвитку.The article focuses on the fact that with the advent of Polish authority in this region educational activity expands and becomes an important factor in national life, spreads its influence on the development of various spheres of Ukrainians’ activity. The article highlights the role of romanov branch of Lutsk society «Prosvita» in circulating Ukrainian books and newspapers, in holding measures dedicated to Shevchenko’s days, mother’s day as well as its effort for the development of Ukrainian cooperative movement in the rural. The article shows the influence of romanov branch «Prosvita» on religious life, which promoted gradual ukrainization of religious service; outlines the role of society in the development of national amateur theatre.
Romanov Educational Center in the 1920s -early 1930s
Keywords: Романів; товариство; українське культурне життя; Romaniv; partnership; Ukrainian cultural life; cooperative movement; religion